Axion-meson mixing in light of recent lattice η–η′ simulations and their two-photon couplings within U(3) chiral theory - Rui Gao; Zhi-Hui Guo; J. A. Oller; Hai-Qing Zhou (Journal of High Energy Physics, 2023)
Abstract We study the mixing of the QCD/QCD-like axion and light-flavor mesons π 0, η, η′ within the framework of U(3) chiral perturbation theory up to next-to-leading order in this work. The axion-meson mixing formulas are calculated order by order in the U(3) δ-expansion scheme, namely the joint expansions of the momentum, light-quark masses and 1/N C . We provide axion-meson mixing relations in terms of the π 0–η–η′ mixing parameters and their masses. The recent lattice simulations on the η–η′ systems turn out to be able to offer valuable inputs to constrain the unknown low-energy constants. The relation of the mass and decay constant of the axion is then further explored based on our updated calculations. The two-photon couplings of the light-flavor mesons, together with the axion, are also investigated in the U(3) chiral theory up to next-to-leading order in the δ-counting scheme.